Pin-Hole-Free, Homogeneous, Pure CsPbBr3 Films on Flat Substrates by Simple Spin-Coating Modification - Gupta, Satyajit; Kulbak, Michael; Cahen, David (Frontiers in Energy Research, 2020)
We show a simple modification of spin-coating to obtain pinhole-free, well-covering and uniform films of an all-inorganic Pb-halide perovskite (Pb-HaP), on a flat substrate (i.e., not mesoporous) at standard temperature and pressure. In Pb-HaP-based devices the active film is generally fabricated by spin-coating. This is a challenging task for purely inorganic Pb-HaPs, as, except if nano-crystallites can be used, mostly rough and inhomogeneous thin films with poor optoelectronic quality are obtained. We describe a gas flow-assisted method to fabricate thin conformal films of phase-pure CsPbBr3. First cells made with the resulting CsPbBr3-films, yield solar conversion efficiencies up to 2.5%. Electron beam-induced current measurements of device cross-sections show uniform charge generation profiles, implying ≥ 0.2 μm diffusion lengths. Non-encapsulated devices generate stable photocurrent for > 1 hr under continuous illumination at maximum power in ambient.